Testing Times - Richard, Willis. author. aut Link
XII, 170 p.
Keywords: This book focuses on the delivery of public examinations offered by the main examining boards in England since Victorian England. The investigation reveals that the provision of examinations was as controversial in the nineteenth century as it is today, particularly since the government is now determined to bring in reform. The issues of grade inflation, the place of coursework in marking, and the introduction of technological change all feature in this book. Educational policy is primarily examined as well as some reference to the global scene. The study analyses archival material from a wide range of sources, including those records stored at the National Archives and the London Metropolitan Archives. An emphasis is placed upon the various institutions that contributed to the process, including the Royal Society of Arts, the London Chamber of Commerce, the City of Guilds of London Institute and the University of London. Attention is given to the findings of the Taunton Commission and the Bryce Commission and shorter reports such as the Northcote-Trevelyn Report which served to radicalise entry and recruitment to the Civil Service. The modern GCSE and the plans for I-levels are considered and key observations are made about the efficacy of those examinations offered by Oxford and Cambridge universities and O-levels, A-levels and NVQs, The reader is given every opportunity to benefit enthusiastically in this account of examinations, and those engaged in education, whether teachers, examiners, students or administrators, will be able to gain useful insights into the workings of the examination system.